Analisis Pemblokiran Rekening Sebagai Upaya Pencairan Piutang Pajak Di KPP Pratama Batam Selatan - Putri, Kiki Amalia; Fitriandi, Primandita (Universitas Katolik Soegijapranata, Semarang, 2025)
This study aims to determine the procedures for implementing account blocking, realization and contribution of account blocking in assisting the disbursement of tax receivables at KPP Pratama Batam Selatan, and the obstacles faced in the implementation of account blocking and the efforts made in facing the existing obstacles. The method used is literature research methods through previous journals and laws and regulations and field research methods based on interviews conducted with the Head of Section Audit, Assessment, and Collection and Tax Bailiff and secondary data collection at KPP Pratama Batam Selatan. From the research conducted, it can be concluded that the implementation of account blocking at KPP Pratama Batam is in accordance with PMK 61 Year 2023. The realization of account blocking action at KPP Pratama Batam Selatan for two consecutive years always exceeds the target, but the realization of tax receivable disbursement through blocking action has a “very insufficient” disbursement contribution to the disbursement of receivables and overall revenue of KPP Batam Selatan. Besides that, there are obstacles both from external and internal experienced by KPP Pratama Batam Selatan in the implementation of account blocking